The Woodsmoke women's book of spells : a novel - Greenlaw, Rachel (Avon, an imprint of HarperCollinsPublishers, 2024)
"Carrie Morgan ran from Woodsmoke ten years ago, and the decision has haunted her ever since. Spending a decade painting and drifting around Europe, she tries to forget her family's legacy and the friends she left behind. But the Morgan women have always been able to harness the power of the mountains surrounding the town, and their spells--and curses--are sewn into the soil. The mountains, they say, never forget. Sure enough, when Carrie's grandmother dies and leaves behind her dilapidated cottage, she returns to renovate--certain she will only be there for one winter. She meets Matthieu as the temperature dips, a newcomer who offers to help refurbish the cottage. Before long, and despite warnings from her great-aunt Cora of the old stories, Carrie finds herself falling for the charming stranger. But when the frost thaws in spring, Matthieu goes missing. Carrie is convinced he's real, and he's in danger. As she fights her way across the mountains to find him, she must confront all the reasons why she left Woodsmoke and decide whether the place she's spent the last decade running from is the home she's been searching for"--